MATERNAL FOOD RESTRICTION DURING LACTATION LEADS TO SEX-SPECIFIC BLOOD HYPERTENSION AND CARDIAC REMODELING IN THE OFFSPRING - Keilah Valéria Naves Cavalcante; Marcos Divino Ferreira-Junior,; Ariel Penha Carvalho da Mota; Maria Eduarda Ribeiro da Silva; Jose Antônio Barbosa Lima Sobrinho; Rodrigo Mello Gomes; Gustavo Rodrigues Pedrino (Arquivos do Mudi, 2023)
Dietary restriction during pregnancy and puberty is a risk factor to hypertension onset atadulthood. The aim of this study was to evaluate the effect of maternal malnutrition duringlactation on cardiovascular parameters, in both sexes of rat pups at 120-day-old. Maternalfood restriction lead to arterial hypertension, baroreflex impairment, cardiac remodeling andincreased collagen deposition in the aorta, in adult male offspring. The females did not showfunctional or morphological disruptions. Together, these results show that maternal foodrestriction during lactation promotes cardiometabolic programming, generating cardiovascularalterations in male adult rat offspring, however female offspring present some kind ofcardioprotective effect.